Development of Guidelines for Promoting Civil Service Teachers and Educational Personnel in Applying for the Teachers’ Council of Thailand Awards and Honorary Insignia in Khon Kaen Province - Jooncharoenpattarakul, Tarin (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to study 1) the current operational conditions regarding the selection process of educational professionals for receiving the Teachers’ Council of Thailand awards and honorary insignia in Khon Kaen Provincial Education Office, and 2) develop guidelines for the selection of educational professionals to receive such awards and recognition. The study population comprised Civil Servant Teachers and Educational Personnel in Khon Kaen Province in the fiscal year 2024, The stdudysample consisted of 393 individuals. Data analysis using applying frequency, percentage, mean, and standard deviation for the quantitative data, along with descriptive content analysis for qualitative data. The findings revealed that 1. The overall current operational condition in implementing the selection process for the Teachers’ Council of Thailand awards and honorary insignia, when assessed in relation to the (POLC) management process (Planning, Organizing, Leading, and Controlling), yielded an overall mean score at a moderate level ( = 3.21). Similarly, the management skills dimension recorded an overall mean score at a moderate level ( = 3.23). 2. The Practice Guidelines for Selecting Educational Professional Entrepreneurs to Receive Teachers’ Council Awards in the Provincial Education Secretariat have 7 element, fourteen operational guidelines to strengthen the selection process. These areas include: 1) Planning Included 2 guidelines; 3) Leading Included 2 guidelines; 4) Controlling Included 2 guidelines; 5) Conceptual Skills Included 2 guidelines; 6) Human Relations Skills Included 1 guideline; and 7) Technical Skills Included 3 guidelines. The proposed guidelines serve as a comprehensive framework for improving the efficiency, transparency, and fairness of the selection process for the Teachers’ Council of Thailand awards and honorary insignia in Khon Kaen Province. By integrating effective management processes with targeted skill development, the model aims to elevate professional standards, motivate educational personnel, and reinforce recognition mechanisms that honor exemplary contributions in the field of education.